Mandible bone density evaluation – significance in the aspect of osteoporosis diagnosis - Stagraczyński, Maciej; Męczekalski, Błażej (Menopause Review/Przegląd Menopauzalny, 2007)
Osteoporosis is an important clinical problem both in the diagnostic and therapeutic aspect. There are a limited number of publications concerning changes in maxillary bone and their correlations with osteoporotic changes in other parts of the skeleton. This article contains contemporary knowledge on the osteoporotic changes, diagnostic procedures and relationships between mandibular bone mass and skeletal osteopenia and osteoporosis. The positive effect of hormone replacement therapy on mandible bone mass density is also presented.